2016
DOI: 10.1177/1098612x15621353
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of guar gum-based ronidazole capsules as a treatment forTritrichomonas foetusinfection in cats

Abstract: Objectives The aims of the study were to determine the in vitro drug release of guar gum-coated capsules of ronidazole, and to evaluate the pharmacokinetics and efficacy of this formulation for the treatment of cats naturally infected with Tritrichomonas foetus. Methods The pharmacokinetics of ronidazole were evaluated in five healthy cats and five cats infected with T foetus. In a second step, the clinical efficacy of these capsules was evaluated by a controlled, randomised, double-blind clinical trial perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…After treatment of 12 cats with ronidazole at 30 mg/kg PO q12h, 9 cats tested negative for T. foetus by means of PCR (7 cats) or fecal wet mount (2 cats) . Treatment of 25 T. foetus infected cats with guar gum‐coated ronidazole at 30 mg/kg q24h for 14 days resulted in 21 cats (84%) testing negative for T. foetus by means of PCR performed on a fecal swab . Collectively, these studies are apt to underestimate the prevalence of ronidazole treatment failure because of small fecal sample sizes (eg, swab) and use of tests with lower sensitivity than PCR (wet mount or culture).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment of 12 cats with ronidazole at 30 mg/kg PO q12h, 9 cats tested negative for T. foetus by means of PCR (7 cats) or fecal wet mount (2 cats) . Treatment of 25 T. foetus infected cats with guar gum‐coated ronidazole at 30 mg/kg q24h for 14 days resulted in 21 cats (84%) testing negative for T. foetus by means of PCR performed on a fecal swab . Collectively, these studies are apt to underestimate the prevalence of ronidazole treatment failure because of small fecal sample sizes (eg, swab) and use of tests with lower sensitivity than PCR (wet mount or culture).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of treatment history and specific type of treatment on T. foetus PCR test results has yet to be examined. Based on studies conducted in experimentally infected cats, ronidazole is the only medication effective in eliminating T. foetus infection, but clinical outcome is unclear in cats with naturally occurring T. foetus infection . Treatment failure with ronidazole is suspected to be common but the incidence of this is largely unknown …”
Section: Introductionmentioning
confidence: 99%
“…Ronidazole, 5-chloto-1-methyl-4 -nitroimidazole, and 5-nitrobenzimidazole had frequencies of detection of 100% in the ranges of 5.34-31 ng/L, 0.51-2.19 ng/L and 0.02-3.86 ng/L, respectively, indicating their widespread distribution. Ronidazole is an antimicrobial and anticoccidial drug and is mainly used for the prevention and treatment of histomoniasis and globidiosis in pets and wild birds [41]. Imidazoles and their metabolites may cause cancer and induce organism mutations [42]; thus, their use is strictly controlled, and these compounds have not been reported in JZB or the surrounding sea areas.…”
Section: Antibioticsmentioning
confidence: 99%
“…All three randomised, controlled, blinded studies utilised different doses and dosing schedules of ronidazole. Grellet et al (2017) used 30 mg/kg once daily for 14 days, Gookin et al (2006) initially used 10 mg/kg twice daily for 14 days, then 30-50 mg/kg twice daily for 14 days and Lim et al (2012) used 50 mg/kg twice daily for 14 days.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
“…Both Grellet et al (2017) and Lim et al (2012) observed eradication of T. foetus in treated cats at the end of treatment after 14 days of treatment (determined via PCR on rectal swab), however clinical signs of diarrhoea were not examined and there was limited monitoring for recurrence following cessation of treatment. Gookin et al (2006) observed that lower dose (10 mg/kg) ronidazole did initially resolve infection during the treatment period, however all kittens relapsed within 2-20 weeks and required further treatment with 30-50 mg/kg ronidazole twice daily, after which no relapse was observed in the following 21-30 weeks and diarrhoea resolved.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%